2018
DOI: 10.1016/j.msea.2017.12.095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature rise on microstructural evolution during high-pressure torsion

Abstract: Dynamic recrystallization occurs at room temperature during high-pressure torsion (HPT) leading to the formation of ultrafine grains with high angles of misorientation. There are questions concerning whether dynamic recrystallization occurs due to the temperature rise during severe plastic deformation or due to the effect of lattice defects. In this study, the real temperature rise was measured by directly placing a thermocouple separately on disc samples of tin, aluminum, silver, copper and titanium. The meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 39 publications
2
43
0
1
Order By: Relevance
“…Several studies have reported the occurrence of recrystallization and an increase in the fraction of Σ3 boundaries in Cu due to adiabatic heating during the HPT process . However, the temperature rise calculated from Equation is not sufficient to introduce dynamic softening during HPT processing which is in agreement with earlier studies reporting the same findings …”
Section: Discussionsupporting
confidence: 88%
“…Several studies have reported the occurrence of recrystallization and an increase in the fraction of Σ3 boundaries in Cu due to adiabatic heating during the HPT process . However, the temperature rise calculated from Equation is not sufficient to introduce dynamic softening during HPT processing which is in agreement with earlier studies reporting the same findings …”
Section: Discussionsupporting
confidence: 88%
“…It should be noted that a temperature increase during HPT processing is critical in terms of atomic diffusion. However, in practice a very recent report demonstrated very limited temperature increases in the very early stages of HPT processing and a saturation at <1 turn under 2.0 GPa for several metals including Al, Ag, Cu, Fe, Sn, and Ti . Moreover, an earlier study on processing of Al and Mg disks by HPT also showed only a limited temperature increase up to 10 HPT turns at 6.0 GPa .…”
Section: Discussionmentioning
confidence: 90%
“…Recent research has shown that the refinement of tungsten grain size can improve its mechanical properties, such as the enhancement of its ductility [9][10][11][12]. Many methods have been proposed to refine the grain size, such as equal channel angular extrusion (ECAE) [13,14], high-pressure torsion (HPT) [15,16], accumulative roll bonding (ARB) [17,18], surface mechanical attrition treatment (SMAT) [19,20], and high-energy ball milling [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%